A comparative study of functional MRI in predicting response of regional nodes to induction chemotherapy in patients with nasopharyngeal carcinoma - Zhao, Dawei; Fang, Xuemei; Fan, Wenjun; Meng, Lingling; Luo, Yanrong; Chen, Nanxiang; Li, Jinfeng; Zang, Xiao; Li, Meng; Guo, Xingdong; Cao, Biyang; Wu, Chenchen; et al. (Frontiers in Oncology, 2022)
Purpose: To identify and compare the value of functional MRI (fMRI) in predicting the early response of metastatic cervical lymph nodes (LNs) to induction chemotherapy (IC) in nasopharyngeal carcinoma (NPC) patients. Methods: This prospective study collected ninety-four metastatic LNs from forty consecutive NPC patients treated with IC from January 2021 to May 2021. Conventional diffusion-weighted imaging, diffusion kurtosis imaging, intravoxel incoherent motion, and dynamic contrast-enhanced magnetic resonance imaging were performed before and after IC. Parameters maps: apparent diffusion coefficient(ADC), mean diffusion coefficient(MD), mean kurtosis (MK), Dslow, Dfast, perfusion fraction (PF), Ktrans, Ve, and Kep) of the metastatic nodes were calculated by the Functool post-processing software. All LNs were classified as responding group (RG) and non-responding group (NRG) according to Response Evaluation Criteria in Solid Tumors 1.1. The fMRI parameters were compared before and after IC and between RG with NRG. The significant parameters are fitted by Logistic regression analysis to produce a new predictive factor predicted probabilities(PRE). Logistic regression analysis and receiver operating characteristic curves (ROC) were performed to further identify and compare the efficacy of the parameters. Results: After IC, the mean values of ADC, MD, Dslow significantly increased, while MK, Dfast, and Ktrans values decreased dramatically, while no significant difference was detected in Ve and Kep. Compared with NRG, PF-pre and Ktrans-pre values in RG were higher statistically. The areas under the ROC for the pretreatment PF, Ktrans, and PRE were 0.736, 0.722, 0.810 respectively, with the optimal cutoff value of 222×10-4, 934×10-3 /min, and 0.6624 respectively. Conclusions: The pretreatment fMRI parameters PF and Ktrans showed promising potential in predicting the response of the metastatic LNs to IC in NPC patients.